Dosage assessment of valnemulin in pigs based on population pharmacokinetic and Monte Carlo simulation. Issue 4 (21st January 2015) - Yuan, L. G.; Tang, Y. Z.; Zhang, Y. X.; Sun, J.; Luo, X. Y.; Zhu, L. X.; Zhang, Z.; Wang, R.; Liu, Y. H.
<x xml:space="preserve">Abstract</x> To estimate the valnemulin pharmacokinetic profile in a swine population and to assess a dosage regimen for increasing the likelihood of optimization. This study was, respectively, performed in 22 sows culled by p.o. administration and in 80 growing‐finishing pigs by i.v. administration at a single dose of 10 mg/kg to develop a population pharmacokinetic model and Monte Carlo simulation. The relationships among the plasma concentration, dose, and time of valnemulin in pigs were illustrated as Ci, v = X0(8.4191 × 10‐4 × e−0.2371t + 1.2788 × 10−5 × e−0.0069t) after i.v. and Cp.o = X0(−8.4964 × 10−4 × e−0.5840t + 8.4195 × e−0.2371t + 7.6869 × 10−6 × e−0.0069t) after p.o. Monte Carlo simulation showed that T>MIC was more than 24 h when a single daily dosage at 13.5 mg/kg BW in pigs was administrated by p.o., and MIC was 0.031 mg/L. It was concluded that the current dosage regimen at 10–12 mg/kg BW led to valnemulin underexposure if the MIC was more than 0.031 mg/L and could increase the risk of treatment failure and/or drug resistance.